Quantizing a relativistic free-particle on the light front: some subtle aspects - Suzuki, A. T.; Sales, J. H. O.; Zambrano, G. E. R. (Natl Research Council Canada-n R C Research Press, 2006)
We use the light-front machinery to study the behavior of a relativistic free particle and obtain the quantum commutation relations from the classical Poisson brackets. We argue that their usual projection onto the light-front coordinates from the covariant commutation relations show that there is an inconsistency in the expected correlation between canonically conjugate variables time x(+) and energy p(-). This incompatibility between canonical conjugate variables in the light front is discussed in the context of Poisson brackets and a suggestion is made on how to avoid it.